KEMALA BHAYANGKARI åˆä¸äºŒå¹´çº§å¦ç”Ÿçš„æ±‰å—ç¬”ç”»ä¹¦å†™åè¯¯åˆ†æž - Safitri, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦ åœ¨ä¹¦å†™æ±‰å—ä¸ï¼Œæ±‰å—ç¬”ç”»åˆ†ä¸ºä¸¤ç§åŸºæœ¬ç¬”ç”»å’ŒæŠ˜ç¬”ç¬”ç”»ã€‚å†™æ±‰å—ç¬”ç”»è¦ æ³¨æ„ä¸€äº›è§„åˆ™å¦‚ç¬”ç”»çš„å½¢çŠ¶ï¼Œç¬”ç”»çš„å˜å½¢å’Œç¬”é¡ºçš„è§„åˆ™ã€‚å› æ¤å¦ç”Ÿå¸¸å¸¸å‡ºçŽ°Â Â  åè¯¯ã€‚æ±‰å—ç¬”ç”»åè¯¯åˆ†ä¸ºç¬”ç”»ç¬”å½¢åè¯¯å’Œç¬”é¡ºè§„åˆ™åè¯¯ã€‚ æœ¬æ–‡é€‰æ‹©Kemala Bhayangkari åˆä¸äºŒå¹´çº§å¦ç”Ÿä½œä¸ºå¯¹è±¡ï¼Œåˆ†æžä»–ä»¬çš„ç¬”ç”»ä¹¦å†™åè¯¯ç±»åž‹å’Œæ‰¾å‡ºç¬”ç”»ä¹¦å†™åè¯¯åŽŸå› ã€‚æœ¬æ–‡ä½¿ç”¨æµ‹è¯•é¢˜å’Œè°ƒæŸ¥é—®å·æ¥ç ”ç©¶ã€‚é€šè¿‡ä¸Šè¿°çš„æµ‹è¯•å’Œè°ƒæŸ¥ç»“æžœå¯å¾—çŸ¥ï¼Œæœ€é«˜çš„å¹³å‡çŽ‡æ˜¯ç¬”å½¢ä¸å®Œæ•´ã€‚æ±‰å—ç¬”ç”»åè¯¯åŽŸå› æœ‰å››ä¸ªæ–¹é¢ï¼›å—æœ¬èº«ã€æ•™æã€æ•™å¦å½±å“å’Œå¦ä¹ ç–ç•¥ã€‚ å…³é”®è¯ : æ±‰å— æ±‰å—ç¬”ç”» ä¹¦å†™åè¯¯ Abstract In writing Chinese characters, writing the Chinese character strokes should pay attention to some rules such as the rules of writing form of scratches, scrapes shape changes in writing, and the writing sequence rule scratches. Chinese character strokes is divided into two parts, namely the basic strokes and scratches buckling. This causes the students often wrong in writing Chinese characters. This error can be divided into two parts, namely the form of scratches and fault error writing sequence scratches. The author chooses the students of Kemala Bhayangkariâ€™s Junior High School as research objects. This study aimed to analyze the forms of writing errors Chinese character strokes and analyze the factors that influence the writing errors scratches. To achieve the objectives author uses the method of questions and questionnaires. By using the method and questionnaire about the authors obtained data that the error form is incomplete the highest error. The factors that influence the error in the writing of scratches, the scratches Mandarin, instructional materials or textbooks that are used in the process of teaching, learning methods, and the students' learning process. Â  Keywords: Hanzi,Â Â Â Â  Scratches Mandarin,Â Â Â Â Â  Writing mistake